STUDI LITERATUR PERANAN SEKUEN DWI-STIR DAN DWI-SPAIR PADA PENCITRAAN MRI BREAST DENGAN KASUS LESI PAYUDARA - Assa Watari Joan; Maghfirotul Iffah; Nyoman Supriyani; I Putu Eka Juliantara; Kadek Yuda Astina (Perhimpunan Radiografer Indonesia (PARI), 2022)
Background: Breast cancer is the most common case in Indonesia. One of the modalities for detecting breast cancer is MRI. The DWI sequence is one of the sequences used in MRI Breast. In breast DWI, the use of effective fat suppression techniques is essential. Several studies have stated that the most common fat suppression techniques used in breast MRI are STIR and SPAIR, because they are considered capable of optimally displaying lesion images. Signal intensity and image quality depend on fat suppression technique, the choice of method used for breast DWI should be considered, because it can affect lesion identification and ROI for calculating ADC used to differentiate benign and malignant lesions. Methods: This study is a literature review study with descriptive qualitative research type. Collect and analyze library sources from several published data. After being reduced based on the topic, 6 main relevant articles were found to be used as a basis to review, describing and discussing the results according to the topic and then criticizing according to the author's view and determining conclusions. Results: The results of this study showed that DWI-STIR and DWI-SPAIR on MRI Breast imaging have use in suppressing fat and can show the difference between benign and malignant lesions of the breast. With the difference in DWI-SPAIR, the results of SNR and CNR are higher, and DWI-STIR, the results are more homogeneous. Conclusion: DWI-STIR and DWI-SPAIR can suppress fat and differentiate lesions well. DWI-SPAIR is better for lesion visibility on high-tesla MRI, and DWI-STIR is better for low-tesla MRI.